A putative serine/threonine protein kinase encoded by the segment-polarity fused gene of Drosophila. - Preat, T.; Therond, P.; Lamour-Isnard, C.; Limbourg-Bouchon, B.; Tricoire, H.; Erk, I.; Mariol, M.C.; Busson, D. (Nature, 1990)
The segmented pattern of the Drosophila embryo depends on a regulatory cascade involving three main classes of genes. An early regulatory programme, set up before cellularization, involves direct transcriptional regulation mediated by gap and pair-rule genes. In a second phase occurring after cellularization, interactions between segment-polarity genes are involved in cell communication. Segment-polarity genes are required for pattern formation in different domains of each metamere and act to define and maintain positional information in each segment. The segment-polarity gene fused is maternally required for correct patterning in the posterior part of each embryonic metamere. It is also necessary later in development, as fused mutations lead to anomalies of adult cuticular structures and tumorous ovaries. Here we provide molecular evidence that this gene encodes a putative serine/threonine protein kinase, a new function for the product of a segmentation gene. This result provides further insight into segment-polarity interactions and their role in pattern formation.